The Concept of ‘Home’ in Palestinian Diaspora Fiction: A Critical Study of Randa Jarrar’s Fiction - Jameel Ahmed Alghaberi (Langkawi: Journal of The Association for Arabic and English, 2018)
The paper discusses the concepts of ‘home’, ‘cultural identity’, and ‘transnationalism’ in Randa Jarrar’s fiction. Being a diasporic Palestinian American, Randa Jarrar in her debut novel A Map of Home presents a particular view of ‘homeland’ and of what ‘historic Palestine’ means to her. The attempt in this paper is to critically analyze her fiction and to highlight the issues that she tackles as a writer of Palestinian origin. The paper also explores the way Randa Jarrar approaches the concept of ‘home’, and an examination of the relationship between Palestinian diasporas and their homeland-Palestine is presented. There is much wandering that Randa Jarrar is experimenting with in rather a creative space, and there is also a counter-narrative ideology embedded in the novel, a way to resist the stereotypes that have fixed the Middle Eastern female body as propagated in Orientalist discourse.